2021
DOI: 10.3389/fpls.2021.718932
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Apogamous Species of Woodferns Show Different Protein and Phytohormone Profiles

Abstract: The gametophyte of ferns reproduces either by sexual or asexual means. In the latter, apogamy represents a peculiar case of apomixis, in which an embryo is formed from somatic cells. A proteomic and physiological approach was applied to the apogamous fern Dryopteris affinis ssp. affinis and its sexual relative D. oreades. The proteomic analysis compared apogamous vs. female gametophytes, whereas the phytohormone study included, in addition to females, three apogamous stages (filamentous, spatulate, and cordate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 132 publications
(164 reference statements)
1
8
0
Order By: Relevance
“…Out of 879 quantifiable proteins [27], we detected a large number (417) that are shared by the gametophytes of apomictic DA and its sexual parent DO. These results, together with a previous study using the same two species [27], enlarge the proteomic profile of both ferns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 879 quantifiable proteins [27], we detected a large number (417) that are shared by the gametophytes of apomictic DA and its sexual parent DO. These results, together with a previous study using the same two species [27], enlarge the proteomic profile of both ferns.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 879 quantifiable proteins [27], we detected a large number (417) that are shared by the gametophytes of apomictic DA and its sexual parent DO. These results, together with a previous study using the same two species [27], enlarge the proteomic profile of both ferns. However, unlike for DA [25], transcriptome data for DO are lacking, such that most certainly fewer proteins could be identified in DO than in DA due to sequence divergence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetative and reproductive development of ferns is underexplored compared with other plant groups. In this regard, the most studied aspects in ferns are: photomorphogenesis (Wada, 2007), spore germination (Salmi et al, 2005; Suo et al, 2015), cell polarity (Salmi and Bushart, 2010), cell wall composition (Eeckhout et al, 2014), reproduction (Kaźmierczak, 2010; Lopez and Renzaglia, 2014; Valledor et al, 2014; de Vries et al, 2016; Domzalska et al, 2017; Grossmann et al, 2017; Rivera et al, 2018; Wyder et al, 2020; Fernández et al, 2021; Ojosnegros et al, 2022; 2023), or adaptation to the environment (Gill et al, 2009; Thagela et al, 2016; Sareen et al, 2019). In particular, these studies show that ferns are able to survive atmospheric conditions with a higher amount of carbon dioxide than we have now, and to resist in situations of salinity, drought, or soil contamination with heavy metals (Rathinasabapathi, 2006; Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Our sequence alignments reveal that the BR receptor-like proteins in ferns are more closely related to seed-plant BRL2, which cannot bind BRs. Yet, active BRs and physiological responses to BRs have been detected in ferns [ 26 , 27 , 33 ], so how BRs function in ferns remains unknown. We found that although the presumed BR receptors in Ceratopteris richardii (C-fern) cannot directly complement the dwarf phenotype of Arabidopsis bri1 mutants, their heterologous expression in Arabidopsis can activate BR responsive genes, indicating that they may have weak BR functions.…”
Section: Introductionmentioning
confidence: 99%